Inclusion and exclusion in the European public sphere - Bruell, Cornelia (Javnost (Ljubljana), 2012)
Can transnational public spheres be envisaged for Europe, which, in fact, create accountability - that is, spaces of critical articulations, control mechanisms, and political correctives to the governing levels? Can the political, as a critical force and the willingness to struggle and decide, be re-introduced into the public sphere? In which ways are race/ethnicity, class and gender cleavages being (re)presented and articulated in the public sphere and how do they intersect? In attempting to answer these questions, we aim this article at exploring the potential for a European discursive space pertaining to issues of gender and diversity. The empirical focus is on the views of political parties and social movements that are participating in public debates. Addressing the inclusions and exclusions in the European public sphere at the intersections of gender and racial/ethnic minorities, we look at the shifts in rhetoric, discourses and policies. As a result, we find common discursive patterns on the intersections between ethnicity and gender which, however, can at best be interpreted as a sign of the emergence of broader European public spheres. Only if these debates can be generalised, European public spheres fulfilling the functions of creating accountability and control mechanisms can develop.
Keywords: Javna sfera; Public sphere; Manjšine; Minorities; Social exclusion; Družbena izključenost; Europe; Evropa; javnost; družbena gibanja; political party; politične stranke; oblast; authority; družbena neenakost